Tinjauan Pustaka: Analisis Komposisi Rasa dalam Cairan Elektronik Menggunakan GC-MS dan Potensi Dampaknya terhadap Kesehatan Pernapasan - Shalsa Septia Zulni; Mochammad Yuwono; Rury Eryna Putri; Aghnia Nabila; Rachmadi Azhar Fathoni (Acta Chimica Asiana, 2026)
The use of electronic cigarettes (e-cigarettes) has increased substantially in recent years as an alternative to conventional tobacco smoking. E-liquids, the core component of these devices, are formulated with various flavoring chemicals to enhance user experience. However, these flavoring agents may pose potential health risks when inhaled. This study aims to systematically review the chemical constituents of e-liquid flavorings identified using Gas Chromatography–Mass Spectrometry (GC-MS). A comprehensive literature search was conducted through PubMed, Google Scholar, and ScienceDirect databases, focusing on articles published within the past ten years. The analysis concentrated on identifying chemical compounds present in a range of e-liquid flavors, including vanilla, bubble gum, coffee, tobacco, strawberry, lemon, and cannabis. The findings indicate that e-liquids commonly contain compounds such as vanillin, ethyl maltol, cinnamaldehyde, benzaldehyde, and limonene. While these substances are generally recognized for their aromatic and flavor-enhancing properties, several have been associated with adverse respiratory effects. Upon heating, these flavoring compounds undergo thermal degradation, producing harmful carbonyl derivatives such as formaldehyde and acetaldehyde. Both compounds are classified as human carcinogens by the International Agency for Research on Cancer (IARC). Nicotine, frequently present in e-liquids, contributes to addictive behavior and is associated with increased risks of psychological disorders. Additionally, certain studies have reported the presence of diethyl phthalate, likely introduced through contamination from packaging materials. This review highlights the critical need for stricter regulation of flavoring agents in e-liquids to mitigate their potential toxicological impact. Standardized testing and safety evaluations should be mandated prior to product approval. Furthermore, more rigorous scientific investigations are required to assess the long-term health effects of chronic exposure to inhaled flavoring chemicals. The study also underscores the importance of raising public awareness regarding the potential dangers of vaping and supports the development of comprehensive policies to control the chemical composition of e-cigarette products.